Appeal decision on MAS-AirAsia case : a commentar - Abdul Rahman, Nasarudin; Ahamat, Haniff (Sweet & Maxwell, Thomson Reuters, 2016)
In 2012 the Malaysia Competition Commission (“MyCC”) took action against the biggest airlines in Malaysia, Malaysia Airlines System Bhd (“MAS”) and AirAsia Bhd for breaching the Competition Act 2010 (“CA 2010”) by entering into a market sharing arrangement. MyCC imposed a financial penalty of RM10 million on each enterprise and the enterprises appealed against the MyCC’s decision to the Competition Appeal Tribunal (“CAT”). In 2014 the CAT issued a landmark decision in favour of the appellants and set aside the decision of the MyCC. The aim of this article is to analyse the reasons for the appeal decision and how the CAT interpreted the competition provisions embodied in the CA 2010. This paper argues among others that the CAT’s decision has a great impact on the manner in which the MyCC performs its duties especially in dealing with hardcore restrictions which fall under the “object” category.